Isothermal solid-phase recombinase polymerase amplification on microfluidic digital versatile discs (DVDs)1. Issue 38 (30th April 2015) - Tortajada-Genaro, Luis A.; Santiago-Felipe, Sara; Amasia, Mary; Russom, Aman; Maquieira, Ángel
<x xml:space="preserve">Abstract</x> The proposed device, for massive DNA-based screening in limited-resource settings, comprises a centrifugal platform to perform isothermal solid-phase amplification in microarray format and a digital versatile disc drive to read the results.